Reliability of Ultrasonographic Measurement of Cervical Multifidus Muscle Dimensions during Isometric Contraction of Neck Muscles - Somayeh Amiri Arimi; Asghar Rezasoltani; Seyed Yaghoub Sakhaei; Seyed Mehdi Tabatabaei; Minoo Khalkhali (Shahid Beheshti University of Medical Sciences, 2012)
Background and Aim: Cervical multifidus is considered as one of the most important neck stabilizers. Weakness and muscular atrophy of this muscle were seen in patients with chronic neck pain. Ultrasonographic imaging is a non-invasive and feasible technique that commonly used to record such changes and measure muscle dimensions. Therefore, the aim of this study was to evaluate the reliability of ultrasonographic measurement of cervical multifidus muscle's dimensions during isometric contraction of neck muscles. Materials and Method: Ten subjects (5 patients with chronic neck pain and 5 healthy subjects) were recruited in this study. Cervical multifidus muscle's dimensions were measured at the level of forth cervical vertebrae. Ultrasonographic measurement of cervical multifidus muscle at rest, 50% and 100% of maximal voluntary contraction (MVC) were performed by one examiner within 1 week interval. The dimensions of cervical multifidus muscle including cross-sectional area (CSA), anterior posterior dimension (APD), and lateral dimension (LD) were measured. Intraclass correlation coefficients (ICC), standard error of measurement (SEM) and minimal detectable change (MDC) were computed for data analysis.Results: The between days reliability of maximum strength of neck muscles and multifidus muscle dimensions at rest, 50% and 100% of MVC of neck muscles were good to excellent (ICC=0.75-0.99).Conclusion: The results of this study showed that ultrasonographic measuring of cervical multifidus muscle's dimensions during isometric contraction of neck muscles at the level of C4 in females with chronic neck pain and healthy subjects is a reliable and repeatable method.